Pengaruh Digital Payment dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Pbb-P2 (Studi Kasus Desa Kebalen, Kecamatan Babelan) - Vina Zafira Damayanti; Suparno Suparno; Eva Maria Sulastri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of digital payment and service quality on taxpayer compliance with Rural and Urban Land and Building Tax (PBB-P2) in Kebalen Village, Babelan District, Bekasi Regency. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 100 taxpayers selected using simple random sampling technique. The data analysis method used is multiple linear regression with the assistance of the SPSS program. The results show that digital payment partially has a positive and significant effect on PBB-P2 taxpayer compliance, while service quality partially does not have a significant effect on taxpayer compliance. Simultaneously, digital payment and service quality have a significant effect on PBB-P2 taxpayer compliance. These findings indicate that the ease of access to tax payments through digital systems can improve taxpayer compliance in fulfilling their tax obligations.